The Effectiveness of Vitamin C for Postoperative Pain Relief in Patients Undergoing Laparoscopic Cholecystectomy: A Prospective Randomized Double-blind Trial - Renu Bala; Ram Murti Saini; Shashi Kiran; Priyanka Bansal; Kirti Kshetrapal; Pulkita Kataria (Indian Journal of Pain)
Background: Laparoscopic cholecystectomy is associated with postoperative pain in the upper and lower abdomen, back, and shoulder region which persist for 2–3 days. Vitamin C is a powerful reductant with antioxidant, neuroprotective, and neuromodulation effects. It is successfully used in complex regional pain syndrome and few surgeries. In the present study, its effect on postoperative pain after laparoscopic cholecystectomy has been assessed. Materials and Methods: The present, prospective, randomized double-blind study was conducted following approval from the institutional ethics committee. Sixty adult patients either sex, the American Society of Anesthesiologists I or II were randomized to group C who received 1 g Vitamin C intraoperatively, whereas Group N received normal saline (control group). Standardized anesthesia protocol was followed in all patients. Postoperative pain was assessed as per the numeric rating scale. For rescue analgesia acetaminophen, ketorolac and diclofenac were given. Follow-up period was 24 h after surgery. Results: The demographic profile was comparable into two groups. Postoperative pain scores were lower in Group C as compared to Group N. There was reduced demand for rescue analgesic in Group C. None of the patients reported any adverse event. Conclusion: A single dose of 1 g Vitamin C intraoperatively helped in obtunding pain following laparoscopic cholecystectomy with no side effects. Hence, it may be incorporated as a component of multimodal analgesic regimen.